Prenatally traumatized mice reveal hippocampal methylation and expression changes of the stress-related genes Crhr1 and Fkbp5 - Plank, Anne-Christine; Frey, Stefan; Basedow, Lukas Andreas; Solati, Jalal; Canneva, Fabio; von Hörsten, Stephan; Kratz, Oliver; Moll, Gunther; Golub, Yulia (Translational Psychiatry, 2021)
In our previous study, we found that prenatal trauma exposure leads to an anxiety phenotype in mouse pups, characterized by increased corticosterone levels and increased anxiety-like behavior. In order to understand the mechanisms by which aversive in utero experience leads to these long-lasting behavioral and neuroendocrine changes, we investigated stress reactivity of prenatally traumatized (PT) mice, as well as the expression and methylation levels of several key regulatory genes of the stress axis in the dorsal hippocampus (dHPC) of the PT embryo and adult mice. We detected increased corticotropin-releasing hormone receptor 1 (Crhr1) and decreased FK506 binding protein 5 (Fkbp5) mRNA levels in the left dHPC of adult PT mice. These alterations were accompanied by a decreased methylation status of the Crhr1 promoter and an increased methylation status of the Fkbp5 promoter, respectively. Interestingly, the changes in Fkbp5 and Crhr1 mRNA levels were not detected in the embryonic dHPC of PT mice. Together, our findings provide evidence that prenatal trauma has a long-term impact on stress axis function and anxiety phenotype associated with altered Crhr1 and Fkbp5 transcripts and promoter methylation.
CRIS-Team Scopus Importer:2021-04-09